Znachenie razvitiia funktsii reguliatsii i kontrolia u mladshikh shkol'nikov pri korrektsii disgrafii - Aleeva I. V. (Modern education development: theory, techniques and practice, 2020)
theoretical substantiation of the importance of correcting the difficulties of the functions of regulation and control of activity. The relationship of this function with the writing skill is shown and examples of errors in regulatory dysgraphia are given.
Keywords: письмо; младшие школьники; дисграфия; primary school children; writing; регуляторная дисграфия; регуляция деятельности; Dysgraphia; regulatory dysgraphia; regulation of activities